PENERAPAN METODE THINK PAIR SHARE DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD - hidayah, nur (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Think Pair Share Metodh in Increasing Mathematics Learning of 4th Grade Student Elementary School. The purpose of this research to increase mathematics learning of fourth grade student elementary school by application of think pair share method. This research is a collaborative classroom action research was conducted in 3 cycles. Each cycle consist of planning, action, observation, and reflection. Subjects were all students in the fourth grade elementary school. The sourse data used are students, teacher, colleague, and researcher. Data collection techniques are test techniques and non test techniques. The validity of data using triangulation technique and triangulation of data collection technique. The conclusion of this research is the application of think pair share method can increase mathematics learning of fourth grade student elementary school. Keywords: think pair share method, Mathematics learning Abstrak: Penerapan Metode Think Pair Share dalam Peningkatan Pembelajaran Matematika Siswa Kelas IV SD. Tujuan penelitian ini adalah untuk meningkatkan pembelajaran Matematika siswa kelas IV SD dengan penerapan metode think pair share. Penelitian ini merupakan penelitian kolaboratif yang dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah seluruh siswa kelas IV SD. Sumber data yang digunakan adalah siswa, guru, teman sejawat dan peneliti. Teknik pengumpulan data dilakukan dengan teknik tes dan non tes. Validitas data menggunakan teknik triangulasi sumber dan triangulasi pengumpulan data. Simpulan penelitian adalah penerapan metode think pair share dapat meningkatkan pembelajaran Matematika siswa kelas IV SD. Kata kunci: metode think pair share, pembelajaran Matematika